Differential Impact of Acute and Chronic Stress on CA1 Spatial Coding and Gamma Oscillations - Tomar, Anupratap; Polygalov, Denis; McHugh, Thomas J. (Frontiers in Behavioral Neuroscience, 2021)
Chronic and acute stress differentially affect behaviour, as well as the structural integrity of the hippocampus, a key brain region involved in cognition and memory. However, it remains unclear if and how the facilitatory effects of acute stress on hippocampal information coding are disrupted as the stress becomes chronic. To examine this, we compared the impact of acute and chronic stress on neural activity in the CA1 subregion of male mice subjected to a chronic immobilization stress paradigm. We observed that following first exposure to stress (acute stress), the spatial information encoded in the hippocampus sharpened and the neurons became increasingly tuned to the underlying theta oscillation in the local field potential (LFP). However, following repeated exposure to same stress (chronic stress), spatial tuning was poorer and the power of both the slow-gamma (30-50 Hz) and fast-gamma (55-90 Hz) oscillations, which correlate with excitatory inputs into the region, decreased. These results support the idea that acute and chronic stress differentially affect neural computations carried out by hippocampal circuits and suggest that acute stress may improve cognitive processing.